Salt Stress induced changes in growth, pigments and protein contents in two horse gram [Macrotyloma uniflorum (Lam.) Verdc] varieties - C. Sathish, G. Kanagaraj* and (Journal of Scientific Agriculture, 2017)
Growth parameters and photosynthetic pigments changes in horse gram were investigated under salinity of different concentrations (0, 40, 80. 120mM). The two horse gram varieties Paiyur-2 and CO-1 were sampling was done in young and fully matured leaves were taken from control and salinity treated plants on 15th Days After Treatment (DAT) and 30th DAT. Treatments were planted in pots. Growth parameters such as plant height, lea area, fresh and dry weight of the whole plants decreased in both varieties under salinity stressed condition. Photosynthetic pigments such as total chlorophyll, chlorophyll ‘a’ chlorophyll ‘b’ were significantly reduced in the salinity stressed leaves. Quantitative differences with response to salinity. Were also noticed in the content of soluble protein in two horse gram varieties. Our data revealed that Paiyur-2 maintained lower reduction of growth and higher contents of photosynthetic pigments as well as soluble protein content when compared to variety CO-1 during the adverse effect of salinity stress.